A modified method for measuring the calcaneal moment arm on weight-bearing computed tomography - Zhu1 , Mingjie; Sempson, Sera; Gu, Wanjun; Wang , Chao; Sun, Songmin; J Hunt , Kenneth; S Myerson, Mark; Li, Shuyuan (Journal of the Foot & Ankle, 2024)
Objective: This study introduced a modified weight-bearing computed tomography to measure the calcaneal moment arm (WBCTCMA) and compared the CMA values between the original and modified techniques. Methods: The WBCT scans of 10 healthy feet were loaded in the CubeVue software, correctly oriented in the transverse plane. Instead of using a specific single coronal cut of the tibia, as in the original WBCT-CMA method, the modified method includes the full thickness of the tibia in the coronal plane to better define the tibia axis. The CMA of each foot was evaluated using both methods. Intraclass correlation coefficient (ICC) model was used to assess the intra- and interobserver reliabilities of both techniques. Results: There was no statistically significant difference between the CMA values generated from the two measurement techniques (p = 0.99). Both methods demonstrated excellent intra- and interobserver reliabilities (0.93 and 0.97 for the modified WBCT-CMA, and 0.93 and 0.94 for the original WBCT-CMA). Conclusion: The modified WBCT-CMA is equivalent to the original WBCT-CMA in both intra- and interobserver reliabilities. Instead of using a relatively shorter tibia from one specific single cut, as in the original technique, the modified WBCT-CMA provides a reconstructed tibia with a longer and clearer shaft for measurement. This has the potential advantages of being easy to perform and less time-consuming, also reducing errors. Level of Evidence III; Retrospective comparative study.